Long‐term changes in drought indices in eastern and central Europe. (24th June 2021) - Jaagus, Jaak; Aasa, Anto; Aniskevich, Svetlana; Boincean, Boris; Bojariu, Roxana; Briede, Agrita; Danilovich, Irina; Castro, Fernando Domínguez; Dumitrescu, Alexandru; Labuda, Martin; Labudová, Lívia; Lõhmus, Krista; et al.
Abstract: This study analyses long‐term changes in drought indices (Standardised Precipitation Index—SPI, Standardised Precipitation–Evapotranspiration Index—SPEI) at 1 and 3 months scales at 182 stations in 11 central and eastern European countries during 1949–2018. For comparative purposes, the necessary atmospheric evaporative demand (AED) to obtain SPEI was calculated using two methods, Hargreaves‐Samani (SPEIH) and Penman‐Monteith (SPEIP). The results show some relevant changes and tendencies in the drought indices. Statistically significant increase in SPI and SPEI during the cold season (November–March), reflecting precipitation increase, was found in the northern part of the study region, in Estonia, Latvia, Lithuania, northern Belarus and northern Poland. In the rest of study domain, a weak and mostly insignificant decrease prevailed in winter. Summer season (June–August) is characterized by changes in the opposite sign. An increase was observed in the north, while a clear decrease in SPEI, reflecting a drying trend, was typical for the southern regions: the Czech Republic, Slovakia, Hungary, Romania, Moldova and southern Poland. A general drying tendency revealed also in April, which was statistically significant over a wide area in the Czech Republic and Poland. Increasing trends in SPI and SPEI for September and October were detected in Romania, Moldova and Hungary. The use of SPEI instead of SPI generally enhances drying trends. Abstract : Trend analysis of drought indices in central and eastern Europe during 1949–2018 indicated that the moisture regime has been mostly stable. Significant increasing trends were found in the northern part of the study region reflecting the general increase in precipitation. Summer season is characterized by changes of the opposite sign in drought indices (figure) showing a drying tendency in some southern regions (Czech Republic, Romania, Moldova, Hungary and southern Poland).